Caracterização limnológica e distribuição espacial de insetos aquáticos, das ordens Ephemeroptera, Plecoptera e Trichoptera, na bacia do Rio Meia Ponte, Goiás, Brasil - SILVEIRA, Flávio Luiz de Souza (2003)
The Meia Ponte River is one of the most important water sources in Goiás State, supplying water for almost half of its population. However, its watershed has been strongly affected by intense agriculture practice, cattle breeding, and industrial and domestic effluent discharges. In this paper, 34 sites in this watershed were chosen to the development of a limnological study. In the first chapter, the limnological characterization of these sites is presented, including 20 physical-chemical, microbiological and physiographic variables, during the rainy and dry seasons of 2001. The sites located at the Meia Ponte River downstream from Goiânia municipality showed the worst water quality. Temporal and spatial patterns were observed. In the second chapter, the influence of abiotic factors on Ephemeroptera, Plecoptera and Trichoptera community was accessed during the dry season of 2001. Physiographic variables were the most important factor for community variation (mainly substrate type and water velocity). Physical-chemical variables had a secondary effect on community structure.